Research on the Talent Cultivation Path of Aesthetic Education Practice Workshop in College Student Communities in China —Taking Suzhou Institute of Technology as an Example (Journal of Global Arts Studies, 2025)
Background: The practice of aesthetic education in colleges and universities has some problems, such as the single form, insufficient combination with traditional culture, low participation of students and lack of systematic talent training mode. Objective: Through the analysis of teaching in local undergraduate colleges, the problems in the practice of aesthetic education in colleges are discussed, and the talent training path of community aesthetic education workshop in local undergraduate colleges is explored. Methods: Based on the background of the construction of university student community, this paper focuses on the innovative carrier of aesthetic education practice workshop, and analyzes it from the dimensions of competition and creation leading, intangible cultural heritage empowerment, special promotion, evaluation system construction and achievement application. Results: This paper discusses the talent training path of the community aesthetic education workshop for college students, which provides theoretical reference and practical reference for deepening the reform of aesthetic education and improving the quality of talent training in colleges and universities. Conclusion: To promote college students from cultural cognition to identity, craft to inherit, hands-on creation to labor education, feel the spirit of art craftsman, improve aesthetic accomplishment, and promote the construction of aesthetic education in colleges and universities.
Keywords: Aesthetic Education; Student Community; Practical Workshop; Talent Cultivation